Case Report: Intensive Inpatient Neurorehabilitation Achieves Sustained Real-World Benefits in Severe Alcohol-Related Wernicke-Korsakoff Syndrome: A Case Study With 7-Years Follow-Up - Schrader, Mareike; Bamborschke, Stephan; Lenk, Ute; Sterr, Annette (Frontiers in Psychology, 2021)
About 85% of survivors of acute Wernicke’s Encephalopathy (WE), a frequent and serious consequence of thiamine deficiency and alcohol misuse, sustain chronic neurocognitive deficits also known as chronic Wernicke-Korsakoff syndrome (WKS). If alcoholism is combined with smoking, tobacco alcohol, optic neuropathy (TAON) may occur which leads to visual impairment. In contrast to WKS, TAON may be treated successfully by early vitamin substitution and detoxification. Little research has been conducted on WKS longterm outcomes. Existing literature suggests poor prognosis. Symptoms remaining beyond the acute treatment with thiamine are thought to be irreversible. Whether neurorehabilitation may be an effective route to help recovery of those persistent symptoms is an open question. At our neurorehabilitation center, which specialises in the treatment of severe chronic deficits after brain injury, the opportunity arose to treat a 35 year old male with WKS, and to conduct follow-up assessments three and seven years post discharge respectively. Initially MK was admitted to emergency care with suspected postconcussive syndrome, alcohol-related thiamine deficiency and TAON. Thiamin, cobalamin and folate substituion improved TAON but major cognitive deficits remained. When admitted to our center four months later, he was fully reliant on care staff for all activities of daily living (ADL). Through intensive neurocognive training and psychological treatment he improved gradually and, after 26 months, was well enough to be discharged into the community and pursue work in a sheltered setting. Neuropsychological tests, as well as patient reports obtained at the follow ups showed that the benefits apparent at discharge had been sustained, and for some scores, improved further. This was particularly evident in the Rey-Osterrieth Complex Figure Test which improved from percentage ranges <1 for immediate recognition and recall at discharge to rank 16 for immediate recognition and rank 5 for recall at the seven year follow-up. This case study illustrates the immense benefits neurorehabilitation can have for WKS induced by alcohol misuse. It further demonstrates how skills and strategies, learned in the inpatient setting, translate into living well and independently, and how the latter promotes further improvement long after discharge.